2013
DOI: 10.1186/2193-1801-2-390
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of heavy metal (Cu, Ni, Fe, Co, Mn, Cr, Zn) pollution in effluent dominated rivulet water and their effect on glycogen metabolism and histology of Mastacembelus armatus

Abstract: The present study was conducted to examine the contamination of rivulet situated at Kasimpur, Aligarh (27.218° N; 79.378° E). It receives the wastewater of Harduaganj Thermal Power Plant (HTPS) containing fly ash and heavy metals. Among the heavy metals estimated in the rivulet water, Fe (8.71 mgL-1) was present in the highest concentration followed by Cu (0.86 mgL-1), Zn (0.30 mgL-1) Mn (0.21 mgL-1), Ni (0.12 mgL-1), Co (0.11 mgL-1) and Cr (0.10 mgL-1). The values for the heavy metals such as Fe, Ni and Mn we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
40
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(48 citation statements)
references
References 18 publications
8
40
0
Order By: Relevance
“…Such alteration can cause shortening of lamellar length and hence a decrease in the blood-water diffusion area (Garcia-Santos et al 2006), and it was previously reported for catfishes (Clarias macrocephalus and C. gariepinus) exposed to Cd (Pantung et al 2008). The alterations observed in the gills of chub from the Zletovska River were probably caused by chronic fish exposure to mining effluents, since it has been reported that severe gill damages, such as necrosis, occur following the chronic exposure to toxicants, and are more frequently observed after exposure to heavy metals or complex mixtures of environmental pollutants than after exposure to organic pollutants (Mallatt 1985;Poleksić and Mitrović-Tutundžić 1994;Takashima and Hibiya 1995;Triebskorn et al 2008;Javed and Usmani 2013).…”
Section: Resultsmentioning
confidence: 97%
“…Such alteration can cause shortening of lamellar length and hence a decrease in the blood-water diffusion area (Garcia-Santos et al 2006), and it was previously reported for catfishes (Clarias macrocephalus and C. gariepinus) exposed to Cd (Pantung et al 2008). The alterations observed in the gills of chub from the Zletovska River were probably caused by chronic fish exposure to mining effluents, since it has been reported that severe gill damages, such as necrosis, occur following the chronic exposure to toxicants, and are more frequently observed after exposure to heavy metals or complex mixtures of environmental pollutants than after exposure to organic pollutants (Mallatt 1985;Poleksić and Mitrović-Tutundžić 1994;Takashima and Hibiya 1995;Triebskorn et al 2008;Javed and Usmani 2013).…”
Section: Resultsmentioning
confidence: 97%
“…Javed and Usmani [77,78] in their study on Mastacembelus armatus thriving in water reservoir reported that fish exhibited the influence of effluents from coal fired Thermal Power Plant releasing Cu, Ni, Fe, Co, Mn, Cr and Zn. The exposed fish showed significant decrease in tRBC count (2.16 9 10 6 mm -3 ), significant increase in tWBC count (3.84 9 10 3 mm -3 ) and insignificant decrease in Hb (9.48 gdL -1 ) when compared to control.…”
Section: Nickel (Ni)mentioning
confidence: 99%
“…However, the existence of toxic heavy metal ions in the wastewater pose a health hazard to animals and the environment (Cormier & Muller, 2000). Agricultural activities, sewage, industrial disposal and even natural disasters have constantly increased the amount of heavy metal ions in the aquatic ecosystems (Javed & Usmani, 2013). Generally, heavy metals are stable under ambient environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Although the human body needs some of these metal ions in trace quantities, their existence in high concentrations can result in serious human ailments (Rammika, Darko, & Torto, 2011). Henceforth, it is essential that the concentration of heavy metal ions in recycled wastewater be considerably reduced to acceptable levels as set out by international monitoring agencies such as the World Health Organization (WHO) (Javed & Usmani, 2013), Food and Agriculture Organization (FAO) (Elnabris, Muzyed, & El-Ashgar, 2013) and Environment Protection Agency standard (EPA) (Barakat, 2011).…”
Section: Introductionmentioning
confidence: 99%